Size/density compensation in Chloris gayana Kunth cv. Fine Cut subjected to different defoliation regimes - Martinez Calsina, Luciana; Agnusdei, Monica Graciela; Assuero, Silvia Graciela; Perez, Hector Eduardo (Wiley, 2019)
The study evaluated the plasticity of Chloris gayana Kunth cv. Fine Cut to defoliation in terms of tiller size/density compensation (SDC). Twelve mini‐swards were grown in a greenhouse under non‐limiting water and nutrient availabilities for 188 d. Four defoliation treatments were applied as a factorial arrangement of two defoliation frequencies and intensities: 80L, 80H, 100L and 100H (80 and 100 denote percentage of photosynthetically active radiation intercepted at defoliation; L and H denote stubble LAIs of 0·6 and 1·75, respectively). Tiller density, demography, dry weight, leaf area and volume were determined over the final 77 d of the experiment. SDC was observed across 80H and both 100 treatments. The estimated slope of the relationship between tiller size and density was close to −5/2, the deviation from the −3/2 line proposed for undefoliated swards being related to changes in LAI and tiller leaf area/volume ratio. The most severe defoliation regime, 80L, resulted in a lower tiller population density relative to the compensation line, suggesting that this defoliation management shifted the species beyond its range of phenotypic plasticity. Cumulative herbage production was significantly reduced in 80L. Despite the similar herbage production of 80H and both 100 treatments, the former was the most favourable defoliation regime for optimizing leafiness and productivity.